Mangrove Vegetation Mapping with Remote Sensing Approach (Citra Landsat 8) in Lhokseumawe City - Imamshadiqin, Imamshadiqin; Nurmayana, Nurmayana; Imanullah, Imanullah; Syahrial, Syahrial; 'Akla, Cut Meurah Nurul; Salmarika, Salmarika; Fuadi, Afdhal (Universitas Teuku Umar, 2024)
One of the best potential mangrove forests is located in Lhokseumawe City. Mangrove forests function as protected areas in coastal areas and are used as vegetation whose existence must be maintained. Efforts to protect it can be carried out by mapping the distribution of mangrove forest areas as a database in Lhokseumawe City. Mapping the distribution of mangrove forest areas can be done using remote sensing. This research was conducted in October - November 2022 in Lhokseumawe City. The method used in this study is the visual interpretation of remote sensing imagery and field surveys. Visual interpretation techniques are used to find out the extent of information from satellite imagery in 2022 which has been geometrically corrected regarding mangrove forest vegetation. Field surveys are needed to obtain more accurate data results. The results of research on mangrove vegetation in Lhokseumawe City are found in 4 sub-districts, namely: Muara Satu District, Banda Sakti District, Muara Dua District, and Blang Mangat District with a total area of ± 65.74 Ha. The results of the density level of mangroves in Lhokseumawe City are dominantly rare with a value of 0.32 m2